The Usborne science encyclopedia - Robson, Kirsteen (Usborne Publishing Ltd London, 2015)
SCIENCE & TECHNOLOGY: GENERAL INTEREST (CHILDREN'S / TEENAGE). A comprehensive science reference book covering key topics from particle physics to genes and DNA, with clearly written explanations and superb photographs and illustrations. QR codes for each topic provide instant access, via a mobile device, to over 180 video clips of experiments and animated lessons that enhance the information in the book. Ages 5+